An engineered human IgG1 CH2 domain with decreased aggregation and nonspecific binding - Guangcan Cao; Xinyu Gao; Yancheng Zhan; Qingguang Wang; Zhe Zhang; Dimiter S. Dimitrov; Rui Gong (Taylor & Francis Group, 2020)
The immunoglobulin (Ig) CH2 domain is a promising scaffold for the development of candidate therapeutics. We have previously shown that the stability of isolated CH2 could be increased by the introduction of an additional disulfide bond and removal of seven N-terminal residues (m01s). However, both isolated CH2 and m01s aggregate, likely due to the existence of aggregation-prone regions (APRs) that we identified by using computational methods. This knowledge was used to generate a phage display library of mutants. The library was incubated at high temperature to remove aggregating CH2 domains, and then panned against a mouse anti-human CH2 monoclonal antibody targeting a conformational epitope to remove misfolded CH2s. After two rounds of panning, one clone, m01s5, with smaller APRs, was identified. After additional mutagenesis one clone, m01s5.4, which aggregated much less than m01s as measured by a turbidity assay and dynamic light scattering, was identified. m01s5.4 also exhibited much lower nonspecific binding than m01s. Engineering of a previously identified m01s-based tumor antigen-specific binder led to a dramatic reduction of its aggregation without affecting its binding. In summary, we describe a new approach for reducing aggregation based on a combination of computational and phage display methodologies, and show that aggregation of CH2-based scaffolds can be significantly reduced by the newly identified mutants, which can improve the developability of potential CH2-based therapeutics.